2020
DOI: 10.3390/insects11090621
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Drosophila suzukii in Coastal and Mainland Sweet Cherry Orchards of Greece

Abstract: Despite the recent invasion and wide spread of Drosophila suzukii Matsumura (Diptera: Drosophilidae) in Europe, little is known regarding its population trends in coastal areas of the southern Mediterranean countries. Using adult trapping and fruit sampling, we studied the population dynamics of D. suzukii in coastal and mainland (semi-highland) cherry orchards of Greece, from 2018 to 2020. Adults were captured in traps baited with apple cider vinegar, placed in conventional and unmanaged sweet-cherry orchards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
2
3
1
Order By: Relevance
“…In another study, we found a similar late-season higher D. suzukii population trend in small fruit crops when monitored using Pherocon D. suzukii Dual-Lure (Trécé Inc., Adair, OK, USA) [36]. The late-season occurrence of D. suzukii in various fruit crops has been reported from regions abroad, as well [37,38]. Monitoring traps in this study also caught another newly invasive species of Drosophilidae, Zaprionus indianus Gupta, 1970, and many other fruit flies and other dipterans during sampling.…”
Section: Resultssupporting
confidence: 67%
“…In another study, we found a similar late-season higher D. suzukii population trend in small fruit crops when monitored using Pherocon D. suzukii Dual-Lure (Trécé Inc., Adair, OK, USA) [36]. The late-season occurrence of D. suzukii in various fruit crops has been reported from regions abroad, as well [37,38]. Monitoring traps in this study also caught another newly invasive species of Drosophilidae, Zaprionus indianus Gupta, 1970, and many other fruit flies and other dipterans during sampling.…”
Section: Resultssupporting
confidence: 67%
“…In the laboratory, Tochen et al (2014) observed that at a temperature of 22 o C, the intrinsic rate of population increase of D. suzukii was higher (0.22) when compared to other temperatures in a range from 14 to 28 o C. Evans et al (2018), also in the laboratory, observed that heat stress (>30 o C) can reduce the fecundity and fertility of D. suzukii females. In contrast with our findings, other studies did find that fluctuations in the D. suzukii capture rates were correlated mostly to temperature in orchards of several fruit trees in another region of Brazil, as well as in Greece (Papanastasiou, Rodovitis, Bataka, Verykouki, & Papadopoulos, 2020;Wollmann et al, 2019). In our study, temperature did explain a significant, but mostly small part of the variation in capture rate.…”
Section: Climate Variablescontrasting
confidence: 99%
“…Drosophila suzukii adults were captured throughout the year with spring and late autumn peaks in a coastal area in Greece, which is relatively close to our study region in Türkiye. However, only a single peak was observed in the mainland in autumn (Papanastasiou et al, 2020). In Central Europe, large populations of D. suzukii were observed in September and October, but the species was almost absent before July, and it was suggested that the long-distance migration might be essential for it to re-establish following the high mortality in winter (Deutsch & Kiss, 2021).…”
Section: Resultsmentioning
confidence: 99%